The Analysis of Social Deixis Used in the Downton Abbey and Made in Dagenham Movies Set in the Twentieth Century - Oktiva Herry Chandra (Department of Linguistics, Faculty of Humanities, Diponegoro University, 2022)
Communication plays an essential role for humans in making great conversations where some addressee forms are used by the speakers to give respect to others. The researcher discusses how 20th-century society represents the usage of the addressee form in showing honor or relationship to their interlocutors using social deixis theory by Levinson and social dimensions by Holmes. The study aims to demonstrate the social deixis types used and its reference meaning and explain how external factors influence social deixis forms in Downton Abbey and Made in Dagenham movies set in 20th century. This study focuses on the pragmatic approach conveying the use of linguistic choices by all movie characters. The research design includes the descriptive qualitative type. In collecting the data, the researcher uses non-participatory observation. This research shows that the relational and absolute social deixis type existed in the movie characters' utterances in 20th-century society. However, the Authorized Speaker type of absolute social deixis is not found in both movies. Beside that, this study discovers all components of social dimensions that could figure the social factors which influenced the characters' addressee forms: solidarity, relative status, formality, and two functional scales.Keywords: social deixis, pragmatics, movie, social dimension, social factor